(3QSGdI aj GNJdGa GdbQGAs - (3Gdbej, eMeO SYjO GdTQja, cGf MjG aj SfI (B1099(3g`s
(3ChdgG (B:s
(3HSe Gddg (B...(3GdMeO ddg GdPj fLe GdbQBf hSnqHY Pdc GdJHjGf(B...(3GYdehG ENhGfj aj GdOjf hNdGfj aj WdH Gdjbjf(B...(3MbjbI GdGNJdGa GdhGbY aj GdbQGAGJ GdSHY(B...s
(3BNQgG (B:s
...(3bGd Gddg JYGdi hgh CUOb GdbGFdjf (B((3hChMi QHc Edi GdfMd(B) (3ceG aj GdbQBf GdeHjf, hbO hQO GdNHQ Yf GdCFeI GdWGgQjf(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B603s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs